The Sensors Connectivity within SCADA Automation Environment and New Trends for Security Development during Multicasting Routing Transmission. (26th October 2015) - Shahzad, Aamir; Udagepola, Kalum Priyanath; Lee, Young-keun; Park, Soojin; Lee, Malrey
This study examined the security of SCADA system and its protocols, more specifically, SCADA/DNP3 protocol security. To achieve the study goals, a SCADA simulation environment is designed for water pumping process through connectivity of intelligent sensors, the payload is constructed, and security is deployed inside DNP3 protocol stack and then bytes are multicast to subcontrollers.